Influence of Treated Natural Jute Fiber on Flexural Properties of Reinforced Concrete Beams - Murugan.R, Bharathi; Gayke, Ajit; C, Natarajan; M.K, Haridharan.; G, Murali; K, Parthiban (International Journal of Engineering and Technology, 2018)
India is one of the largest producers of jute, its potential use in many branches of engineering should be developed for the prosperity of the nation. The recent trends in utilizing the natural fibers has increased due to its advantages over synthetic fibers due to low cost, low environment hazard and easy availability. The properties of the fiber is improved by treating the jute fiber with alkali and latex polymer. Since, very few studies been conducted using the treated jute fiber concrete, an experimental work was carried with 0.6% as optimum percentage of treated jute fibers based on the mechanical properties of concrete. The influence of flexural characteristics of concrete was compared with control beams and beams cast with fibers in whole area and also only in tension zone of beam for M20 and M25 concrete grade. The beams with fibers of whole area had better strength, stiffness characteristic than the control beam and the beam with fibers in tension zone only. The initial cracking load was increased by 12.92% and 11.23 % and ultimate load was increased by 6.94% and 7. 20% for the beams cast with fibers in whole area for M20 and M25 grade of concrete, respectively.Â Â